Dinâmica do gás ionizado em núcleos ativos de galáxias de baixa luminosidade - Heckler, Kelly Frank (2024)
Active galactic nuclei (AGNs) are associated with energetic events triggered by the feeding of the supermassive black hole present in the nucleus of galaxies. The AGN feedback process is responsible for influencing the growth of the host galaxy by impacting star formation. In early-type galaxies, relativistic radio jets are produced in a radiatively inefficient accretion disk, causing a slow growth of the black hole without considerably influencing the star formation of the host galaxy. This maintenance mode feedback is associated with low-luminosity AGNs, such as LINERs. Spiral and dwarf galaxies, on the other hand, experience phases of radiatively efficient accretion of matter, triggered mainly by major mergers, causing a rapid growth of both the black hole and the galaxy. In these regimes, high-luminosity AGNs are formed through radiative feedback processes, strongly influencing star formation in the host galaxy. With the advancement of integral-field spectroscopy, it is now possible to resolve regions close to black holes, which until recently was not possible. This is especially important for low-luminosity AGNs, since it is necessary to resolve the circumnuclear region of galaxies to understand how feedback processes influence the growth of the host galaxy in these luminosity regimes. Thus, in this Ph.D. thesis, the general objective is to investigate the influence that feedback has on the host galaxy by searching for outflows signatures in the kinematics of the ionized gas of earlytype galaxies and nearby dwarf galaxies, hosts of low-luminosity AGNs. Ionized gas outflows have been found in five early-type galaxies. However, they are not powerful enough to affect the galaxy growth on a large scale since the kinetic efficiencies obtained are less than or equal to 0.01%, however they are capable of heating and redistributing the gas in the circumnuclear region.